PENYULUHAN KESEHATAN TENTANG PENYAKIT TIDAK MENULAR PADA MASYARAKAT KELURAHAN PANYURAN, KEC. PALANG, KABUPATEN TUBAN - Wahyu Tri Ningsih; Tanty Wulan Dari; Moch Bahrudin; Teresia Retna Puspitadewi; Binti Yunariyah; Wahyuningsih Triana Nugraheni; Roudlotul Jannah; Su'udi; Yasin Wahyuriyanto; Titik Sumiatin; Siti Maimuna (Jurnal Abdi Masyarakat, 2025)
Hypertension and diabetes are of concern because of their high prevalence and their role as major risk factors for heart and blood vessel disease. The aim of this community service is to increase public knowledge and awareness of the importance of prevention and early detection of Non-Communicable Diseases.Methods used in this community service are through counseling and interactive discussions. The target is the community of Panyuran Village, Palang District, Tuban Regency. The media used is leaflets. The results of this community service are increased public knowledge and awareness of Non-Communicable Diseases, especially diabetes mellitus and hypertension, as well as prevention and early detection. Counseling activities can be carried out continuously in collaboration with local health centers and health cadres. Monitoring of activities that have been carried out needs to be carried out periodically by conducting examinations of people at risk of experiencing Non-Communicable Diseases by local health cadres.